Chemical study of the medicinal plant "Toe" (Datura sanguinea (R.& P.) D. Don) - Reyna Pinedo, Víctor (2007)
From the leaves, flowers and seeds of the Toe or "Misha Toro" (Datura Sanguino (R. & P.) D.Don), a plant collected in the Province of Huancabamba (Department of Piura, in the northern highlands of Peru) was isolated the alkaloid scopolamine, which was identified by its mass spectra, RMN1H and RMN13C. In addition, the qualitative analysis of the secondary metabolites and the quantification of alkaloids present in the different organs of this plant were carried out.